Web-Based Decision Support System For Selecting The Best Paripurna Mosque In Pekanbaru City Using The Simple Additive Weighting (SAW) Method - Aisyah Rizki Utari; Octadino Haryadi (Yayasan Ibrahim Learning Centre Agam, 2025)
This study aims to develop a web-based decision support system (DSS) used to determine the best full-service mosque in Pekanbaru City. This system uses the Simple Additive Weighting (SAW) method, which is capable of managing assessments from various criteria, such as facilities, worship activities, cleanliness, services, and mosque management. The system was designed using the Rapid Application Development (RAD) approach and tested through the black-box method and manual calculation validation. The implementation results show that the system can provide accurate and objective ranking results based on the highest preference values of 20 sample mosques. In addition, user testing results show a satisfaction level of 83%. This system is considered effective in supporting the transparency and efficiency of the process of selecting the best mosques and can be accessed online by the public and authorities.